Detection of group A beta-hemolytic Streptococcus employing three different detection methods: culture, rapid antigen detecting test, and molecular assay - Santos Odimara; Weckx Luc Louis Maurice; Pignatari Antonio Carlos Campos; Pignatari Shirley Shizue Nagata (Brazilian Journal of Infectious Diseases, 2003)
In order to study the prevalence of Group A beta-hemolytic Streptococcus (GABHS) pharyngotonsillitis in our pediatric population and to compare different sampling methods of GABHS detection, oropharyngeal swabs from 50 children with acute pharyngotonsillitis, between 1 and 12 years old, were used simultaneously for culture, molecular assay and rapid GABHS antigen detection tests. All children were clinically examined at the Division of Pediatric Otorhinolaryngology of the Federal University of São Paulo. Diagnostic criteria were based on signs and symptoms, including sore throat, fever and oropharyngeal purulent secretion. Children that had been treated with antibiotics were excluded. Overall, combining the three methods, the prevalence of GABHS was 34%. GABHS was diagnosed in 30% of the bacterial cultures, in 25% of the samples tested with the molecular nucleic acid hybridization method and in 26% of the cases tested with the rapid antigen detection test. There was no significant difference between these three methods.